GROWING EXCLUSION OF THE MAJORITY: The “Triumph of Wahhabism” and Its Threat to Indonesian Islam in the Democratic Society (JOURNAL OF INDONESIAN ISLAM, 2023)
Although Wahhabi institutions have neither grown rapidly nor attracted a significant number of followers in Indonesia, the spread of Wahhabist thoughts among Indonesian Muslims has outreached the institutions and their propagators. This study proves the argument by examining the rift among a Muslim community in the Eastern Java village of "Karang Mojo", in which Wahhabism penetrates into the lives of the villagers due to exposure to a Wahhabi television station "Rodja”. This Wahhabi televangelism TV channel typically broadcasts religious narratives that exclude and attack the culturally vibrant practices of Indonesian Islam that preserved the tolerance to the local cultures. No prior record was found of the presence of a Wahhabi propagator or institution in the remote village. However, currently, a Muslim group with heavy Wahhabist influence has emerged in the remote village through various channels including Rodja television (hence, the group is hereinafter referred to as Rodjai). Through a series of observations and interviews with a number of people from the various groups in the village, the study points out the powerful influence of Wahhabism that penetrates into not only the urban areas but also the rural villages of Indonesia. The previously-unified Muslim community in the village is now divided. The Rodjai group in the village is very aggressive in attacking the culturally-rich practices of traditional Indonesian Islam and condemning those practices as heretical and superstitious that deviate from the pure teachings of Islam.